(3TQM eKdKGJ bWQHs - (3CHh Ydj eMeO Hf GdeSJfjQ GdeYQha HbWQH GdfMhis; (3CHj Ydj Hf CMeO Hf GdeSJfjQ, bWQH,J (B206 (3g` s
(3ChdgG (B:s
(3GdeKdK efg bWQH hgh GdMQa fQGg ai GdcJGHI hGMOkG hjJUQa Ydi KdGKI ChLg s
(3BNQgG (B:s
(3hGYQVJ UOhQ TehS GdNjd Ud dLGegG JeJ GdQSGdI GdChdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hQO ai cTa GdXfhf L(B2 (3U (B1586 (3Cf GdeKdK ai GddZI gh dCHh Ydi eMeO Hf GdeSJfjQ GdeYQha HbWQH GdfMhi GdeJhai SfI (B206 (3g` s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs